2018
DOI: 10.1038/s41551-018-0290-2
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of macrophages into engineered skeletal muscle enables enhanced muscle regeneration

Abstract: Adult skeletal muscle has a robust capacity for self-repair, owing to synergies between muscle satellite cells and the immune system. In vitro models of muscle self-repair would facilitate the basic understanding of muscle regeneration and the screening of therapies for muscle disease. Here, we show that the incorporation of macrophages into muscle tissues engineered from adult-rat myogenic cells enables near-complete structural and functional repair after cardiotoxic injury in vitro. First, we show that—in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
104
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(120 citation statements)
references
References 84 publications
(136 reference statements)
3
104
0
1
Order By: Relevance
“…We tested this hypothesis by making use of an irradiation protocol typically applied in vivo to deplete/ inactivate the satellite stem cell pool 35,36 and could indeed observe that the endogenous regenerative capacity of ESM in response to CTX-injury was abolished by irradiation, which advances earlier studies by demonstrating that muscle regeneration in vitro is indeed driven by satellite cells reentering the cell cycle. 25 In line with a recent report 38 and findings in other organ models, 50 macrophages may also play a crucial role in skeletal muscle regeneration. Given the muscle origin of the cells used for ESM generation and the presence of macrophages in most, if not all primary cell isolates (refer for example to primary cells isolated from the heart and their use in tissue engineering 30 ), we anticipated and finally confirmed the presence of macrophages in ESM.…”
Section: Discussionsupporting
confidence: 76%
“…We tested this hypothesis by making use of an irradiation protocol typically applied in vivo to deplete/ inactivate the satellite stem cell pool 35,36 and could indeed observe that the endogenous regenerative capacity of ESM in response to CTX-injury was abolished by irradiation, which advances earlier studies by demonstrating that muscle regeneration in vitro is indeed driven by satellite cells reentering the cell cycle. 25 In line with a recent report 38 and findings in other organ models, 50 macrophages may also play a crucial role in skeletal muscle regeneration. Given the muscle origin of the cells used for ESM generation and the presence of macrophages in most, if not all primary cell isolates (refer for example to primary cells isolated from the heart and their use in tissue engineering 30 ), we anticipated and finally confirmed the presence of macrophages in ESM.…”
Section: Discussionsupporting
confidence: 76%
“…To date only a single model has shown any regenerative capacity. This study employed a fibrin/Matrigel® hydrogel system containing primary skeletal muscle myoblasts from rats (Juhas et al, , ). The culture system employed is based upon a bespoke 3D culture mould and uses primary rat myogenic precursor cells (requiring the sacrifice of small laboratory animals), negating some of the advantages associated with using engineered tissues as models.…”
Section: Introductionmentioning
confidence: 99%
“…To date only a single model has shown any regenerative capacity. This study employed a fibrin/Matrigel ® hydrogel system containing primary skeletal muscle myoblasts from rats (Juhas et al, 2014(Juhas et al, , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The tissues generated are functional, contain the mixed cell populations represented in muscle, and demonstrate renewal and even expansion of the Pax7 niche through recovery. Although previous work has shown that engineered muscles can regenerate following injury (Juhas et al, 2014(Juhas et al, , 2018aFleming et al, 2019;Tiburcy et al, 2019), no previous work has demonstrated this with human engineered muscles. The injury sustained following BaCl2 treatment is robust, leading to significant loss of myotubes and function.…”
Section: Discussionmentioning
confidence: 98%
“…The demonstration that these tissues regenerate following chemical insult allows the study of human skeletal muscle regeneration, including cell population dynamics across time, to be undertaken without the need to invasively sample patients repeatedly. In addition, the flexibility of the system allows for future work to build complexity, such as through the addition of immune cells to simulate an inflammatory response (Juhas et al, 2018a) or mechanical/electrical stimulation to capture the effects of post-injury exercise (Aguilar-Agon et al, 2019;Khodabukus et al, 2019). As the complexity and maturity of these models develops, they will present an opportunity to test putative clinical interventions in a high throughput manner on human tissue, adding a novel tool to the preclinical testing tool box to help improve lead screening and ultimately improve healthcare for patients.…”
Section: Discussionmentioning
confidence: 99%